On some features of low-temperature mixed crystallization of CsI solutions obtained from industrial wastes - Boyarintsev, A.Yu.; Cherginets, V.L.; Ponomarenko, T.V.; Rebrova, T.P.; Varich, A.G.; Bryleva, E.Yu.; Koryakina, E.M.; Sheina, T.V.; Varchenko, V.V.; Yurchenko, O.I. (Functional Materials, 2017)
Investigation of multiple low-temperature mixed crystallization (LTMC) of the solution wastes of cesium iodide was reported. LTMC is a very simple and convenient way for an essential decrease of the concentrations of practically all the admixtures including isomorphic ones (Na, K, Rb). However, LTMC results in CsI enriching with Tl, which enters into the crystallized fraction. Due to the presence of considerable amounts of Na and sulfate admixtures during the first 3-4 LTMC the displacement of other admixtures occurs with lower intensity comparing with the following LTMC stages and the threshold concentration of Na is ca. 5·10⁻² mas.%. For Na the effective purification coefficient β is 0.6-0.7 for the initial solution and it reduces to 0.35-0.5 in more pure solutions, for K these values are 0.75 and 0.5-0.55. Na content does not affect Rb distribution and for this admixture β ~ 0.65-0.75 for all the solutions. For Cu the value of β is close to 1 since CuI is insoluble in water and LTMC favors its entering in the solid fraction. β value for Tl admixture is ca. 1.06 that means the enriching of the final product of LTMC with respect to this admixture. The removal of sulfates from CsI using LTMC occurs very easy.